Juz 'Amma Publications for Kids in Indonesia: A Study of Authorship, Presentation, and Interpretation Approaches - Salamah, Ika Hilmiatus; Miski, Miski (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2024)
This article examines the widespread publication of Juz 'Amma for children, highlighting the lack of extensive research on this topic. It focuses on three main areas: authorship, presentation, and approach. Using a historical-analytical approach, the study analyses 11 Juz 'Amma publications for children in Indonesia from 2020–2024, revealing that writers or illustrators with limited authority often collaborated to create these publications. In terms of presentation and writing, most use detailed explanations and popular, non-scientific language, with only two offering more general explanations. Methodologically, nine of the publications use visuals to explain words (kata), verses (ayat), or chapters (surah), while the rest use scientific methods. The interpretations mainly feature social, educational, and scientific nuances. Although they often employ a contextual approach, they sometimes revert to textual reasoning. These findings highlight the impact of information technology on the latest interpretations of Juz 'Amma and provide a more comprehensive perspective compared to previous, more fragmented studies.